ANALISIS DINAMIK PADA KOMPONEN FLAP ARMS (FAIRING) PESAWAT NC 212 DI PT. DIRGANTARA INDONESIA - Yanuardi, Endi; Suryadi, Dedi; Supardi, Nurul Iman (UNIB Press, 2025)
Airplanes are one of the safest modes of transportation, to ensure this safetyness an analysis is needed to understand the response of the aircraft components. One of them is the fairing on the flap arms, which is part of the aircraft wing structure, where this component supports the movement of the aircraft's flaps. Fairing will experience loading during takeoff, top speed, and landing. One of the loads that occur on the fairing is air pressure. The use of the finite element ethod (FEM) as a method to determine the response of the fairing after being subjected to dynamic loading. In the take-off condition, the total deformation is mm and the equivalent stress is 5,17 Pa. In the top speed condition, the total deformation is mm and the equivalent stress is 199,04 Pa. Whereas in the landing condition, the total deformation is mm and the equivalent stress is 38,812 Pa.